Immunomodulatory effects of new phytotherapy on human macrophages and TLR4- and TLR7/8-mediated viral-like inflammation in mice - Schapovalova, Olesia; Gorlova, Anna; de Munter, Johannes; Sheveleva, Elisaveta; Eropkin, Mikhail; Gorbunov, Nikita; Sicker, Michail; Umriukhin, Aleksei; Lyubchyk, Sergiy; Lesch, Klaus-Peter; Strekalova, Tatyana; Schroeter, Careen A. (Frontiers in Medicine, 2022)
Background: While all efforts have been undertaken to propagate the vaccination and develop remedies against SARS-CoV-2, no satisfactory management of this infection is available yet. Moreover, poor availability of any preventive and treatment measures of SARS-CoV-2 in economically disadvantageous communities aggravates the course of the pandemic. Here, we studied a new immunomodulatory phototherapeutic (IP), an extract of blackberry, chamomile, garlic, cloves, and elderberry as a potential low-cost solution for these problems given the reported efficacy of herbal medicine during the previous SARS virus outbreak. Methods: The key feature of SARS-CoV-2 infection, excessive inflammation, was studied in in vitro and in vivo assays under the application of the IP. First, changes in tumor-necrosis factor (TNF) and lnteurleukin-1 beta (IL-1β) concentrations were measured in a culture of human macrophages following the lipopolysaccharide (LPS) challenge and treatment with IP or prednisolone. Second, chronically IP-pre-treated CD-1 mice received an agonist of Toll-like receptors (TLR)-7/8 resiquimod and were examined for lung and spleen expression of pro-inflammatory cytokines and blood formula. Finally, chronically IP-pre-treated mice challenged with LPS injection were studied for ‘sickness’ behavior. Additionally, the IP was analyzed using high-potency-liquid chromatography (HPLC)-high-resolution-mass-spectrometry (HRMS). Results: LPS-induced in vitro release of TNF and IL-1β was reduced by both treatments. The IP-treated mice displayed blunted over-expression of SAA-2, ACE-2, CXCL1, and CXCL10 and decreased changes in blood formula in response to an injection with resiquimod. The IP-treated mice injected with LPS showed normalized locomotion, anxiety, and exploration behaviors but not abnormal forced swimming. Isoquercitrin, choline, leucine, chlorogenic acid, and other constituents were identified by HPLC-HRMS and likely underlie the IP immunomodulatory effects. Conclusions: Herbal IP-therapy decreases inflammation and, partly, ‘sickness behavior’, suggesting its potency to combat SARS-CoV-2 infection first of all via its preventive effects.